2006
DOI: 10.4049/jimmunol.177.9.6052
|View full text |Cite
|
Sign up to set email alerts
|

Age and Vitamin E-Induced Changes in Gene Expression Profiles of T Cells

Abstract: T cells are vulnerable to age-associated changes. Vitamin E has been shown to improve T cell functions in the old. We studied gene expression profiles of T cells to better understand the underlying mechanisms of age and vitamin E-induced changes in T cell function. Young and old C57BL mice were fed diets containing 30 (control) or 500 (supplemented) ppm of vitamin E for 4 wks. Gene expression profiles of T cells were assessed using microarray analysis with/without anti-CD3/anti-CD28 stimulation. Genes associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 40 publications
1
51
2
Order By: Relevance
“…is is in contrast to studies done by other groups [9,12,47]; however, higher levels of vita- [16][17][18]. Epidemiological reports and dose-response studies on animals showed that the infectious dose for L. monocytogenes can be low.…”
Section: Discussioncontrasting
confidence: 54%
“…is is in contrast to studies done by other groups [9,12,47]; however, higher levels of vita- [16][17][18]. Epidemiological reports and dose-response studies on animals showed that the infectious dose for L. monocytogenes can be low.…”
Section: Discussioncontrasting
confidence: 54%
“…The antioxidant activity is due not only to the de-activation of free radicals produced by the decomposition of lipid hydroperoxides, but also to the inhibition of lipid hydroperoxide decomposition (Pokorny and Parkányiová, 2005;Makinen et al, 2001). In addition, previous studies have shown that tocopherols have substancial health benefits such as hypocholesteremic, hypolipidemic, anticancer, antiinflamatory and antioxidant properties and slow down the aging process (Ghaffari et al, 2011;Singh and Devaraj 2007;Hau et al, 2006).…”
Section: Tocopherolsmentioning
confidence: 99%
“…Vitamin E has been shown to improve T cell functions in the old. It is reported that gene expression profiles of T cells to better understand the underlying mechanisms of age and vitamin E-induced changes in T cell function (129). According to performed experiments with young and old C57BL mice, 500 ppm of vitamin E supplementation for 4 wks resulted in higher expression of genes involved in cell cycle regulation (Ccnb2, Cdc2, Cdc6) in old T cells.…”
Section: Steroidmentioning
confidence: 99%
“…According to performed experiments with young and old C57BL mice, 500 ppm of vitamin E supplementation for 4 wks resulted in higher expression of genes involved in cell cycle regulation (Ccnb2, Cdc2, Cdc6) in old T cells. Gene expression profiles of T cells were assessed utilizing microarray analysis with/without anti-CD3/anti-CD28 stimulation (129). It has found that vitamin E supplementation resulted in higher up-regulation of IL-2 expression in young and old T cells whereas lower up-regulation of IL-4 expression in old T cells following stimulation and also resulted in higher up-regulation of IL-2 expression in young and old T cells whereas lower up-regulation of IL-4 expression in old T cells following stimulation (129).…”
Section: Steroidmentioning
confidence: 99%
See 1 more Smart Citation